PERTUMBUHAN TIGA SPESIES CACING TANAH AKIBAT PENYIRAMAN AIR DAN PENGAPURAN YANG BERBEDA - Bieng Brata (Program Studi Ilmu Tanah Fakultas Pertanian UNIB, 2006)
This study was conducted in the Zoology of Laboratorium, Biology Departement, Faculty of Mathematics and Natural Science, Bogor Agricultura University for 10 months from August 2000 untill May 2001. The objective of the study was to evaluate the efect of watering and lime levels on the three species of earthworms . The method used in this study was Completelly Randomized Design with three factor ie; (1) species Pheretima sp.E. foetiad and L. rubellus, (2) lime levels (0.2 and 0.4%), and (3) watering levels (0, 10, 20 and 30%) of media weight with three replication. The results of the study showed that; (1) the level of watering of 30% of media weight produced better body weight on E. foetiad and L. rubellus, (2) the level of watering of 10% was hight offspring weight on E. foetiad and L. rubellus, (3) the level of watering of 10% produced better biomass production on E. foetiad and L. rubellus, and (4) the watering of 0% produced hight mortality rate.